Garfield. Volume 1, Complete works, 1978 & 1979 - Davis, Jim, 1945 July 28- (Ballantine Books, 2018)
Presents the complete collection of "Garfield" comic strips from 1978-1979. Features rare archival material and an introduction to the series by creator Jim Davis.